ADAPTATION OF IN VITRO BLACKBERRY PLANTS TO FIELD ENVIRONMENTS - E. A. Dobrenkov; L. G. Semenova; S. E. Dunaeva; Y. V. Ukhatova (Труды по прикладной ботанике, генетике и селекции, 2018)
Iability of blackberry accessions in vivo after in vitro culture storage was analyzed. Phenological development phases of adult plants, crop yield and water regime were studied in the field. Adaptability of the accessions to adverse environmental factors (frost, drought and heat resistance, resistance to fungal infections) was evaluated.